Bali’s Garbage Crisis: What Thoughts Prevent Us to Help? - Gunawan, Gianna Gianella (Lembaga Pengembangan Kinerja Dosen, 2026)
Thousands of metric tonnes of garbage remain unmanaged, and despite available solutions, many people are still reluctant to participate in proper waste disposal. This study aimed to identify the reasons behind the unwillingness of different age groups in Kuta Selatan, Badung, Bali to separate their garbage into biodegradable and non-biodegradable categories. This qualitative research used surveys and interviews for data collection. The survey involved three age groups: adolescents (10–19) with 15 respondents, young adults (20–39) with 15 respondents, and middle adults (40–60) with 11 respondents. Interviews were conducted with two environmental experts, and the data were analyzed using thematic analysis. The results showed that reluctance across age groups stemmed mainly from limited awareness of the environmental benefits of waste separation and the negative impacts of improper disposal. Adolescents additionally cited the lack of strict policies and penalties. Young and middle adults shared similar reasons, mostly linked to insufficient knowledge and low motivation. Environmental experts emphasized the importance of improving public awareness of waste management practices and enhancing waste management infrastructure through additional facilities and better-quality services. Overall, this study highlights the need for stronger policies, improved infrastructure, and increased public education to boost community participation in waste separation in Kuta Selatan.